.12x+.6(x-5)=.01(2x-2)

Simple and best practice solution for .12x+.6(x-5)=.01(2x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .12x+.6(x-5)=.01(2x-2) equation:


Simplifying
0.12x + 0.6(x + -5) = 0.01(2x + -2)

Reorder the terms:
0.12x + 0.6(-5 + x) = 0.01(2x + -2)
0.12x + (-5 * 0.6 + x * 0.6) = 0.01(2x + -2)
0.12x + (-3 + 0.6x) = 0.01(2x + -2)

Reorder the terms:
-3 + 0.12x + 0.6x = 0.01(2x + -2)

Combine like terms: 0.12x + 0.6x = 0.72x
-3 + 0.72x = 0.01(2x + -2)

Reorder the terms:
-3 + 0.72x = 0.01(-2 + 2x)
-3 + 0.72x = (-2 * 0.01 + 2x * 0.01)
-3 + 0.72x = (-0.02 + 0.02x)

Solving
-3 + 0.72x = -0.02 + 0.02x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.02x' to each side of the equation.
-3 + 0.72x + -0.02x = -0.02 + 0.02x + -0.02x

Combine like terms: 0.72x + -0.02x = 0.7x
-3 + 0.7x = -0.02 + 0.02x + -0.02x

Combine like terms: 0.02x + -0.02x = 0.00
-3 + 0.7x = -0.02 + 0.00
-3 + 0.7x = -0.02

Add '3' to each side of the equation.
-3 + 3 + 0.7x = -0.02 + 3

Combine like terms: -3 + 3 = 0
0 + 0.7x = -0.02 + 3
0.7x = -0.02 + 3

Combine like terms: -0.02 + 3 = 2.98
0.7x = 2.98

Divide each side by '0.7'.
x = 4.257142857

Simplifying
x = 4.257142857

See similar equations:

| 6x=208-4(52-1.5x) | | 7y/2-10=4 | | -8=-2(x+7) | | -2-6(2+n)=-6(1+n) | | -7x-24=-9x | | 48j+25=12j-11 | | 6.5n+-3.3(2n+-5)=16 | | 91=98+x | | -4(5y-9)+2(4y+6)= | | -1=-z | | 3x/7+6=9 | | 9x^3-9x^2-4+4= | | 7m+38=-5m-16 | | 6x=208-4(52+-1.5x) | | 5x-1=6x-5 | | 3a-5=-6 | | -2(2+w)=-20 | | -15=6g-3 | | 50x+3=7 | | 42=6x+7 | | x/3-2=5 | | 4(q-5)=16 | | 8a+10b=6 | | 2Y^2+9Y-5= | | 4y=208-6x | | x^3-6x^2+16X=96 | | 2(3x-4)=28 | | 0.5x-1.5=2.5 | | 5.4+-3(4m+3)=45.7 | | 6x+14x=16 | | 2(3x+7)-(x-4)= | | -6y+15=-9 |

Equations solver categories